واقع استثمار الموارد المائية لنهر الفرات وآفاق تطويرها - حمدان, ياسر; الخطيب, محمد مروان (Latakia University Journal -Engineering Sciences Series, 2019)
إن تدهور الموارد المائية في سوريا سوف يجعل حصة الفرد من المياه العذبة في عام 2025 في وضع حرج، وسيزداد الاحتياج المائي للمحاصيل الزراعية نتيجة للتغيرات المناخية. ولعدم إمكانية تغيير هذا الواقع الموضوعي، يتحتم علينا الاهتمام بتحسين إدارة مواردنا المائية، والبحث عن سبل للحد من الهدر في مياه الأنهار، وبشكل خاص مياه نهر الفرات الذي يشكل العمود الفقري للموارد المائية السطحية. حتى الآن لم يتم التوصل إلى اتفاقية دولية لتقسيم الوارد المائي لنهر الفرات، بين ثلاثة الأطراف المتشاطئة؛ بسبب التباين في وجهات النظر حول آلية التقسيم، إضافة إلى تذبذب الجريان خلال العام، ومن عام إلى آخر، ووفقاً للبروتوكول الموقع مع الجانب التركي يوجد حالياً هدر كبير من الوارد المائي الممرر لنهر الفرات، ويعود ذلك إلى البطء الشديد في إنجاز البنى التحتية لاستثمار حصتنا من هذا الوارد المائي (مشاريع ري، والاحتياطي الاستراتيجي للموارد المائية؛ كالخزانات، والبحيرات)، بما يحقق الأمن المائي والغذائي لبلدنا. The decline of water resources in Syria will raise a big question about the proportion of the individual in fresh water by 2025. In fact, the need to water for irrigation will go up because of the climate change. Concerning these issues, we have to control our water resources and minimize the loss especially in what is related to the Euphrates which is the major resource of superficial water in Syria. Unfortunately, there is no International Water Treaty among Turkey, Syria and Iraq about the proportions of the Euphrates because of the discrepancy of implementation of dividing the portions. More over, the instability of water level in the river makes such agreements more difficult. Concerning the Syrian side, there is a big loss in using our portion of the Euphrates because of the slowness of building up the infrastructure to use our portion in irrigation, strategic reserves, reservoirs…etc, to achieve our water and food stability.